2011
DOI: 10.1111/j.1365-3148.2011.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost protocol for the production of autologous serum eye drops by blood collection and processing centres for the treatment of ocular surface diseases

Abstract: Efforts should be made to propagate a similar protocol for the production of ASEs in blood centres capable of collecting and processing blood products, making this service affordable and uniformly accessible to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
0
35
0
1
Order By: Relevance
“…It has been reported that AS can be used safely in both outpatient and inpatient settings, under a strict protocol of preparation and storage (Langnado 2004; Partal 2011). However, even though AS are prepared under sterile conditions on an individual patient basis, researchers have noted risks for contamination and consequent infection during preparation, storage, and use of the drops (Geerling 2004; Lee 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that AS can be used safely in both outpatient and inpatient settings, under a strict protocol of preparation and storage (Langnado 2004; Partal 2011). However, even though AS are prepared under sterile conditions on an individual patient basis, researchers have noted risks for contamination and consequent infection during preparation, storage, and use of the drops (Geerling 2004; Lee 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that AS can be used safely in an outpatient as well as inpatient setting, under a strict protocol of preparation and storage (Langnado 2004; Partal 2011). However, even though AS are prepared under sterile conditions on an individual patient basis, there are risks for contamination, and consequent infection, during the preparation, storage, and use of the drops (Geerling 2004; Lee 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, TGF-β concentrations are five times higher in serum than in tears 6. Therefore, many ophthalmologists prefer to use a 20% dilution of ASE to more closely match the TGF-β concentration in natural tears in order to prevent problems with epithelial cell proliferation 3 40 44…”
Section: Autologous Serum Eye Dropsmentioning
confidence: 99%
“…Liu and colleagues determined that a long clotting time (>120 min), centrifugation at 3000g for 15 min and dilution with balanced salt solution at 12.5–25% best supported cell proliferation, migration and differentiation of corneal epithelial cells 50. Based on this work, Partal and Scott44 proposed a low-cost protocol that would adhere to the US Food and Drug Administration requirements for ophthalmic use of autologous blood products. The estimated cost to supply 3 months of ASE to a patient in a safe manner, excluding costs of microbial testing, was US$195.19.…”
Section: Autologous Serum Eye Dropsmentioning
confidence: 99%